Adult Beliefs About the Migration Motives of Unaccompanied Honduran Youth. Issue 3 (August 2021) - Clark, Amy L.; Williams, James L.
A number of researchers have examined undocumented migration from Central America. This literature lacks information about adult beliefs regarding the motivations of minors who journey from Central America unaccompanied and undocumented. Using data from a recent survey conducted in Honduras, we examine adult Hondurans' beliefs about why unaccompanied minors leave the country unaccompanied. The dependent variable is a dummy variable that measures "why children leave the country." Predictor variables are attitudes toward smuggling, willingness to leave without documentation, deportation experience, age, income, and residence in the northern part of Honduras. Using multinomial logistic regression, we find support for four of the eight hypotheses. Findings indicate that adults from the northern region are most likely to believe minors would leave for reasons associated with undocumented immigration. Those who are younger, with lower incomes, and with less access to sanitation are more likely to believe minors would leave without documentation.